RETRACTED : The Influence of Store Atmosphere, Location and Image of Mere on Dunkin Donuts Repurchase Interest in Pasar Minggu - Vivia Hanisa; Resti Hardini; Kumba Digdowiseiso (Journal of Social Science)
This study aims to analyze the influence of Store Atmosphere, Location and Brand Image on Repurchase Interest in the Sunday Market. This study uses primary data obtained from the distribution of questionnaires of 100 Dunkin Donuts respondents at the Pasar Minggu using Multiple Linear Regression processed using the SPSS method version 24.0. The results showed that between Store Atmosphere, Location, and Brand Image had a positive and significant effect on the Interest in Repurchasing Dunkin Donuts Products in the Pasar Minggu. There is a positive and significant influence between Store Atmosphere, Location and Brand Image on Dunkin Donuts Repurchase Intention at Pasar Minggu. There is a positive and significant influence between Store Atmosphere, Location, and Brand Image on Dunkin Donuts Repurchase Intention in the Sunday Market shows that the better Store Atmosphere, Location, and Brand Image are important parts to increase Purchase Intention Repeat.